I10 Cross-sectional and longitudinal analysis in juvenile huntington disease in italy. (13th September 2016) - Marano, Massimo; Migliore, Simone; Maffi, Sabrina; Consoli, Federica; Squitieri, Ferdinando
Abstract : Background: Juvenile Huntington's disease (JHD), affects onset before age 20. Largest CAG expansions present in infancy (age < 10), with atypical course. The role of mutation and other factors on JHD onset, progression, neuropathology and frequency is still controversial. No therapeutic trials including HD children have been designed so far. Objectives: JHD characterisation to implement young patients recruitment for further therapeutic studies. Methods: We revised JHD patients' files retrospectively, since 2005, the year we started REGISTRY. Cross-sectional data was available for 30 JHD patients, whose we had full medical records (i.e., 10 infantiles), out of 55 JHD (i.e., 13 infantiles). Longitudinal data was available for 10 subjects, who are currently recruited in Enroll-HD study, six of them previously followed-up since REGISTRY. Results: Age-at-onset was defined according to motor or severe cognitive/psychiatric manifestations or both. Infantile and adolescent onset groups showed a CAG mutation size of 83 ± 14 and 58 ± 7 repeats, respectively. Motor presentation was preceded by cognitive/psychiatric symptoms. Infantile cases were featured by remarkable dystonia and drug-resistant epilepsy in more then half cases. Adolescent subjects frequently developed parkinsonism, and their follow-up was challenged by suicide ideation in 4/17. Discussion: Cognitive and behavioural symptoms precede motor manifestations in most JHD cases of even many years, often resulting in an undefined disabling condition. It is therefore possible that the JHD frequency is largely underestimated. Definition of onset criteria is critical to recruit JHD cases in future therapeutic trials.